Fibre Lens : Design, Analysis And Fabrication - Abd Rahman, Faidz (2002)
This thesis examines the coupling efficiency and alignment tolerance between laser diodes and single mode fibres. An approach based on integrated lens or fibre lens has been chosen for this work. The integrated lens is designed and fabricated on the fibre tip, which is then measured for coupling efficiency . The measured results are compared to the theoretical values.